The Influence of Education Using Animated Videos on Dental and Oral Health Behavior in Elementary School Children - Sari, Stella Eka; Farhan, Hira; Gyamera, Ebenezer; Paghubasan, Marivic D. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study was to determine the effect of animated video education on dental and oral health behavior in elementary school-aged children. Methodology: This type of research is quantitative with quasi-experimental one group pretest-posttest design. The population is all students of grades 1-6 SDN 1 Tunggulrejo totaling 66 people, a sample of 57 is obtained using the Probability sampling method with proportional random sampling technique. The independent variable is education using animated videos. The dependent variable is dental and oral health behavior. Data collection using a dental and oral health behavior questionnaire. Data analysis with editing, coding, scoring, and tabulating, tested using the Wilcoxon test. Main Findings: The study found that prior to the intervention, 50.9% of students demonstrated poor dental and oral health behavior. After being given animated video education, 94.7% of students showed good behavior. The Wilcoxon test results indicate a significant improvement with a p-value of 0.000 (p < 0.05), confirming that animated video education had a statistically significant positive effect on students’ health behavior. Novelty/Originality of this study: The novelty of this study lies in the use of animated videos as interactive educational media that are more effective than conventional methods in improving children's dental and oral health behavior. With a narrative visual approach that is appropriate to cognitive development, this study contributes to technology-based health education strategies in schools and families.